Алгоритм ситуационного управления процессом кристаллизации сахара в вакуум-аппарате периодического действия с механическим циркулятором - Кравчук, Анатолий Федорович; Ладанюк, Анатолий Петрович; Прокопенко, Юрий Владимирович (My University, 2008)
In the entry are rated the questions of the system analysis of the suger crystallization process, offered an approach for the vacuum pan management taking into account an object's condition, current situation and stages of the process's development. Are giving graph models of the stages of the crystalization process which are used for the management algorithm working up.
Keywords: стационарное управление; кристаллизация сахара; алгоритм; situational management; crystallization of sugar; algorithm; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка